Magnitude of cytopenias among HIV‑infected children in Bahir Dar, northwest Ethiopia: a comparison of HAART-naïve and HAART‑experienced children - Tsegay YG (HIV/AIDS : Research and Palliative Care, 2017)
Yakob Gebregziabher Tsegay,1,* Agerie Tadele,2 Zelalem Addis,3 Agersew Alemu,4 Mulugeta Melku2,* 1Bahir Dar Regional Health Research Laboratory Center, Bahir Dar, 2Department of Hematology and Immunohematology, 3Department of Medical Microbiology, 4Department of Medical Parasitology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia *These authors contributed equally to this work Background: AIDS, caused by HIV, is a multisystem disease that affects hematopoiesis. The aim of this study was to assess cytopenias among HIV-infected children who had a follow-up at Felege Hiwot Referral Hospital, Bahir Dar, northwest Ethiopia. Methods: An institution-based cross-sectional study was conducted between April and May 2013. Systematic random sampling method was used to select the study participants. Descriptive statistics, independent t-test as well as chi-square and logistic regression were used for analysis. A p-value <0.05 was considered as statistically significant. Results: A total of 224 children (112 highly active antiretroviral therapy [HAART]-naïve and 112 HAART-experienced) participated in the study. The magnitude of anemia, thrombocytopenia, neutropenia, leukopenia and pancytopenia among HAART-naïve HIV-infected children were 30.4%, 9.8%, 8%, 4.5% and 1.8%, respectively. The overall prevalence of anemia, neutropenia, thrombocytopenia, leukopenia and pancytopenia were 29.5%, 8.9%, 8%, 4.5% and 1.4%, respectively. Cluster of differentiation-4 percentage and mean corpuscular volume were significantly different between HAART-experienced and HAART-naïve children. Being of younger age and severely immunosuppressed were risk factors of anemia. Conclusion: Anemia was the most common cytopenia, followed by neutropenia. Severe immunosuppression and younger age were significantly associated with anemia. Therefore, emphasis should be given for investigation and management of cytopenias in HIV-infected children, particularly for those who are immunosuppressed and of younger age. Keywords: anemia, children, cytopenia, HAART, HIV, leukopenia, neutropenia, pancytopenia, thrombocytopenia